4 G/4 G polymorphism of plasminogen activator inhibitor-1 gene increases the risk of diabetic nephropathy. (April 2014) - Xue, Cheng; Nie, Wei; Zhou, Chenchen; Yu, Fei; Wang, Dong-Mei; Dai, Bing; Mei, Chang-Lin
Abstract Diabetic nephropathy (DN) has become the most common pathogenesis of end-stage renal disease. Plasminogen activator inhibitor-1 (PAI-1) plays an important role in the pathogenesis of DN. A meta-analysis was conducted to investigate the association between 4 G/5 G variants in the PAI-1 gene and DN susceptibility. Databases including Pubmed, EMBASE, ISI, etc., were searched to find relevant studies. Odds ratios (ORs) with 95% conﬁdence intervals (CIs) were used to evaluate the strength of associations. Ten studies involving 1366 cases and 1888 controls were included. Significant association between 4 G/4 G variant and DN risk was observed (OR 1.26, 95% CI 1.08–1.48, p = 0.004) in overall populations by the recessive model. 4 G allele was also associated with the risk of DN than the 5 G allele (OR 1.15, 95% CI 1.04–1.27, p = 0.008). In the subgroup analysis performed by the ethnicity, 4 G/4 G polymorphism was significantly associated with DN risk than 4 G/5 G + 5 G/5 G in East Asians (OR 1.42, 95% CI 1.03–1.96; p = 0.03), but not in Caucasians. In the stratiﬁed analysis by types of DM, the results showed significant association between 4 G/4 G variant and DN in Type-2 DM (OR 1.42, 95% CI 1.03–1.96, p = 0.03). In conclusion, 4 G/4 G phenotype of PAI-1 gene may be associated with DN risk. Additional larger studies should be conducted in future analyses.